Financial Contagion and Duration: Evidence from International Financial Markets - Enow, Samuel Tabot (International Journal of Economics and Financial Issues, 2023)
The overlapping claims of susceptible shocks affecting multiple financial markets have been well documented in finance literature. These shocks are channelled through several propagation mechanisms due to global integration. The purpose of this study was to investigate financial contagion and the relative duration effect. A variance decomposition blueprint was applied to achieved the objective of this study for a sample of five financial markets. The sampling timeframe was from January 1, 2017 to 31 December 2018 characterised by pre Covid-19 pandemic era and January 1, 2020 to 31 December 2021 for the Covid-19 pandemic. The results indicate weak endogenous relationship between financial markets before the pandemic. However, significant contagion was observed during the Covid-19 pandemic which last for several periods in some markets. In line with this findings, there may be no portfolio diversification benefits during periods of financial distress. In essence, central banks should implement mechanism absorb economic shocks and facilitate easy access to liquidity during periods of financial distress.